2022
DOI: 10.3390/biomedicines10020418
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Intervention in Acute Ischemic Stroke: History and Evolution

Abstract: Stroke is a leading cause of serious long-term disability in the US. Endovascular therapy (EVT), in the form of mechanical thrombectomy, is now a standard of care for patients with acute ischemic stroke with a large vessel occlusion. This article reviews the evolution of EVT in the management of acute ischemic stroke and how it has led to the concept of tissue window over the widely publicized time window.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…While early trials established the benefit of EVT when used within 6 hours from the onset of symptoms, more recent studies have included patients presenting outside this treatment window 18,19 . The DAWN and DEFUSE 3 trials demonstrated the benefit of reperfusion in selected patients presenting late with salvageable brain tissue 10 . The patients in these studies demonstrated small infarcted core volumes but large ischemic penumbra volumes on imaging; therefore, US and Canadian best practice guidelines recommend that patients being considered for EVT between 6 and 24 hours should meet the CT perfusion DWI criteria used in these trials 20,21 …”
Section: Treatment Time Windows For Evtmentioning
confidence: 99%
See 3 more Smart Citations
“…While early trials established the benefit of EVT when used within 6 hours from the onset of symptoms, more recent studies have included patients presenting outside this treatment window 18,19 . The DAWN and DEFUSE 3 trials demonstrated the benefit of reperfusion in selected patients presenting late with salvageable brain tissue 10 . The patients in these studies demonstrated small infarcted core volumes but large ischemic penumbra volumes on imaging; therefore, US and Canadian best practice guidelines recommend that patients being considered for EVT between 6 and 24 hours should meet the CT perfusion DWI criteria used in these trials 20,21 …”
Section: Treatment Time Windows For Evtmentioning
confidence: 99%
“…12 These early studies demonstrated better clinical outcomes and recanalization rates but a higher rate of symptomatic intracranial hemorrhage (ICH). 10 So began enthusiasm for the development of mechanical devices for clot retrieval.…”
Section: Evolution Of Management Of Lvo Aismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, during the first three hours following the onset of this condition, the application of fibrinolytics achieves a marked reduction in disability in 25% of patients. Mechanical thrombectomy, which is normally only available in specialised centres and presents a heterogeneous international distribution, also increases survival rates and drastically decreases sequelae [ 7 , 8 , 9 , 10 ]. However, a high proportion of strokes are not suitable for any type of reperfusion, and it is these on which our study is focused.…”
Section: Introductionmentioning
confidence: 99%